2007
DOI: 10.1196/annals.1415.040
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin α1 as a Chemopreventive Agent in Lung and Breast Cancer

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Washington Headquarters Services, Directorate for Information Operations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 24 publications
1
22
0
1
Order By: Relevance
“…Moreover, several studies have reported that Ta1 is capable of down-regulating the growth of cancer cells, such as murine B16 melanoma [42], lung cancer [43][44][45] and breast cancer [45]. However, the effect of Ta1 is pleiotropic, and it is usually used in combination with cytokines and chemotherapeutic agents in the treatment of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have reported that Ta1 is capable of down-regulating the growth of cancer cells, such as murine B16 melanoma [42], lung cancer [43][44][45] and breast cancer [45]. However, the effect of Ta1 is pleiotropic, and it is usually used in combination with cytokines and chemotherapeutic agents in the treatment of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism of action of these compounds is thought to be an increase of proinflammatory cytokines, T cell proliferation and differentiation as well as antigen expression on tumor cells resulting in the induction of a tumor-specific cytotoxicity [19,20]. Indeed, preliminary phase II trials of thymostimulin in patients with HCC were notable for their tumor response rate and the occurrence of complete responses, resulting in a median overall survival of up to 11.5 months [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Moody et al investigated the effects of T␣1 on mammary carcinogenesis in fisher rats and found that T␣1 could reduce mammary carcinoma incidence and prolong survival time [52]. In another breast adenoma model, T␣1 increased the survival time in female C3(1)SV40T antigen transgenic mice and fisher rats, but it remained to be determined whether the immune response also increased or not [53]. The antitumor activity of T␣1 was most effective when the lung adenomas were small, which was based on studies proformed by Moody who gave T␣1 daily to A/J mice bearing lung adenoma [53].…”
Section: Antitumormentioning
confidence: 99%